Developing technology enhanced authentic assessment instruments to measure students non cognitive critical thinking dispositions - Pratiwi, Nana Novita; Rasiman, Zubaidah; Munaldus; Fitriawan, Dona (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: Critical thinking is widely recognized as a core competency for 21st-century learners; however, assessment practices in schools continue to prioritize cognitive outcomes through conventional testing methods. As a result, non-cognitive aspects of critical thinking, particularly critical thinking dispositions, remain insufficiently assessed. This study aims to develop and validate authentic assessment instruments that holistically measure students’ non-cognitive critical thinking skills. The instruments were designed to capture dispositional dimensions of critical thinking through a combination of an authentic assessment scale, reflective journals, and discussion observation sheets. Method: This study employed a research and development (R&D) approach using the 4D model consisting of Define, Design, Develop, and Disseminate stages. The development process involved needs analysis, instrument design, expert validation, and limited field testing. Participants included nine expert lecturers, six junior high school mathematics teachers, and one class of junior high school students, selected purposively. Content validity was examined using Aiken’s V, while internal consistency reliability was assessed using Hoyt’s formula. Instrument readability and practicality were evaluated through structured response questionnaires administered to teachers and students, with data analyzed descriptively using percentage scores. Findings: The results indicate that all instruments demonstrated high content validity and strong reliability, with coefficients of 0.834 for the authentic instrument, 0.901 for the reflective journal, and 0.879 for the observation sheet. Readability analysis confirmed suitability for junior high school students. Teacher responses were very high (87.4%–91.3%), and student responses were positive (83.07%–85.5%), indicating good usability and relevance. Significance: This study provides empirically validated authentic assessment instruments that support holistic evaluation of non-cognitive critical thinking skills, offering a meaningful alternative to conventional assessment practices and contributing to the advancement of formative, disposition oriented assessment in contemporary education.